AGAMA DAN ISU-ISU KONTEMPORER DALAM PERSPEKTIF FIQH PROGRESIF - ., Yusdani (Al-Mawarid Jurnal Hukum Islam, 2012)
This article aims to shows the importance of progressive Islamic jurisprudence (fiqh) in Islamic studies atmosphere. Fiqh means a new formulation of Islamic Jurisprudence by perspective of democracy, pluralism and human rights in accordance with todayâs contemporary society. By this article, the author explains deeply theoretical framework, issues, position, and challenge of progressive Islamic jurisprudence and its function in reconstruction toward Islamic studies development. The existence of Progressive Islamic Jurisprudence nowadays aims to makes the rule of Islamic law enforcement in contemporary community. It can be solution in creating civilized society showed by equality among subject of country, justice in action, liberality in belief, and protection for minority rights. Keywords: Agama, Isu-Isu Kontemporer, dan Fiqh Progresif